Neuropathic pain: Definition, assessment and epidemiology - Bouhassira, D. (Revue neurologique, 2019)
Neuropathic pain has been a very active and productive clinical research field over the last 15 years. Studies have concerned multiple aspects of these complex chronic pain syndromes including their very definition, the elaboration of new diagnostic algorithms, the development of specific tools for their screening and measurement and their epidemiology. In this review, we summarize these recent evolutions that have impacted the way these pain syndromes are conceptualized and managed both in daily practice and in the clinical research setting.